Rola i zadania systemów controllingowych w budowie i realizacji strategii rozwoju instytucji banków hipotecznych w Polsce - Lisowski, Mariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article author has presented select aspect of management in mortgage bank. He has described principal stages and actions of management, like special account for identify risk and special methods for measure costs. According to the author controlling is very important in financial institution, also in mortgage bank. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 192-196